2005
DOI: 10.1148/radiol.2372040539
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Liver Fat Quantification at MR Imaging: Comparison of Out-of-Phase Gradient-Echo and Fat-saturated Fast Spin-Echo Techniques—Initial Experience

Abstract: Preliminary results suggest liver fat may be more accurately quantified with fat-saturated fast spin-echo MR imaging than with out-of-phase gradient-echo MR imaging, especially in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
148
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 20 publications
3
148
0
4
Order By: Relevance
“…In subjects with cirrhosis, only the ϮFS imaging was correlated with the histopathology. Variable hepatic iron levels (particularly in cirrhotic patients), which affect the relaxation constants, were discussed as a potential reason for the lower correlation of phase-edited MRI with liver biopsy results (29). This is consistent with the single subject in our study with elevated hepatic iron levels that gave large negative values for phase-edited IHCL.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In subjects with cirrhosis, only the ϮFS imaging was correlated with the histopathology. Variable hepatic iron levels (particularly in cirrhotic patients), which affect the relaxation constants, were discussed as a potential reason for the lower correlation of phase-edited MRI with liver biopsy results (29). This is consistent with the single subject in our study with elevated hepatic iron levels that gave large negative values for phase-edited IHCL.…”
Section: Discussionsupporting
confidence: 89%
“…A strong correlation between IP/OP imaging with histology (27) and MRS (28) has also been reported. Qayyum et al (29) investigated a group of subjects with and without cirrhosis by phase-edited and FS-edited imaging using the spleen as an internal standard on a GE system. They reported that ϮFS imaging was better correlated with histopathology than in-opposite phase imaging in noncirrhotic subjects (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the authors could not determine the results for patients with hepatic steatosis, since these patients were not included in the present sample. This variable should still be evaluated, considering that hepatic steatosis may affect the hepatic parenchyma signal intensity on T2-weighted images with fat-suppression (SPIR), like those utilized in the present study (16) . The evaluation of an objective parameter, for example, the nodule/liver signal ratio could add subsidiary results for the differentiation between cysts and hemangiomas on the different sequences utilized and this is a reason for continuing the present study whose results should be reported in a near future.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of liver biopsy is its sampling variability (Ratziu et al 2009;Qayyum et al 2005). Sampling variability is a relevant limitation of liver biopsy due to the fact that the liver biopsy specimen represent only a very limited part of the whole liver and that histologic lesions of NAFLD/NASH are likely to have a very unevenly distribution in the liver ), even at a macroscopic level.…”
Section: Sampling Variabilitymentioning
confidence: 99%